Implemantasi PBL berbasis Moodle Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik pada Konsep Pencemaran Lingkungan - Hardianty, Sylvie; Hindriana, Anna Fitri (Edubiologica, 2021)
The purposes of this research to find out whether there is an influence on the problem based learning model (PBL) moodle based on critical thinking skills and learning outcomes students on the concept of environmental pollution. The subject of this research is X grade students of SMAN 1 Kawali.. To hone critical thinking skills and student learning outcomes by applying moodle-based PBL in the learning process. The results of the research that there is an effect of moodle-based PBL on critical thinking skills and student learning outcomes on the concept of environmental pollution. Through this research it was revealed that moodle-based PBL was able to improve critical thingking skills and learning outcomes with an N-gain score in the control and experimental classes in the medium category.